Greener, cleaner polymerization of isobutene. Issue 3 (1st September 2013) - Damodaran, Krishnan; Lewis, Stewart P.; Mathers, Robert T.; Qian, Liu; Godugu, Bhaskar
Abstract : Methylaluminoxane (MAO)/silyl halide-based initiator systems greatly improve the sustainability of isobutene (IB) polymerizations by eliminating halogenated solvents, reducing energy consumption and removing the need for postpolymerization purification. These solvent-free systems give rise to moderate yields of high-molecular-weight (MW) polymers at convenient temperatures without conventional toxic solvents. In addition, facile separation of MAO and polyisobutene (PIB) was accomplished with supported MAOs. The resulting system gave enhanced activity and high yields of medium-to-high-MW polymer at temperatures up to ambient. The MW-temperature profile for MAO-based systems approximates that for γ-radiation and perfluoroarylated Lewis acid–based systems; however, the former does not require high-purity monomer and is more economical and easily scalable. Modeling experiments involving 2, 4, 4-trimethyl-1-pentene indicate that silyl halides undergo ligand-exchange type reactions with MAO where halogen attached to silicon is replaced with a methyl substituent from MAO with concomitant production of chloraluminoxane and initiation of cationic polymerization in an ill-defined manner.